“Apparently, women don't know how to operate doors": A corpus-based analysis of women stereotypes in the TV series 3rd Rock from the Sun - Gregori-Signes, Carmen (International Journal of English Studies, 2017)
This paper explores how women stereotypes are discursively evaluated in the TV sitcom 3rd Rock from the Sun by paying attention to the societal, cultural and ideological values they convey. Following recent trends for the study of television series (Bednarek, 2010), the analysis is both qualitative and quantitative, adopting a Corpus-Assisted Discourse Analysis approach (Baker, 2006; Partington, 2004). The contextualised analysis of words that refer to women confirms that the sitcom writers of 3rd Rock from the Sun purposefully resort to stereotyping as a verbal strategy to create humour while conveying negative attitudes towards women.